2004
DOI: 10.1016/j.femsle.2004.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Tuber aestivum and Tuber uncinatum: two morphotypes or two species?

Abstract: Tuber spp. are ectomycorrhizal fungi that establish symbioses with shrubs and trees. Because of their different smell and taste, Tuber uncinatum and Tuber aestivum are two truffle morphotypes with a different market value, but whether or not T. uncinatum and T. aestivum are different taxa is still an open debate among mycologists. In order to identify molecular keys characterizing both T. aestivum and T. uncinatum morphotypes, ITS/RFLPs analyses were carried out on a large collection of samples from all over I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 25 publications
5
44
0
Order By: Relevance
“…The spatial distribution and ecological requirements of these symbiotic fungi vary by species. Some species are widely distributed and have pronounced morphological and molecular variability (9,11,22,25,27,32), while others have a more restricted distribution and little intraspecific polymorphism in either morphological or genetic traits (3,4,8,9,26). Tuber magnatum Pico, which produces white ascomata, is harvested only in Italy and some countries on the Balkan Peninsula.…”
mentioning
confidence: 99%
“…The spatial distribution and ecological requirements of these symbiotic fungi vary by species. Some species are widely distributed and have pronounced morphological and molecular variability (9,11,22,25,27,32), while others have a more restricted distribution and little intraspecific polymorphism in either morphological or genetic traits (3,4,8,9,26). Tuber magnatum Pico, which produces white ascomata, is harvested only in Italy and some countries on the Balkan Peninsula.…”
mentioning
confidence: 99%
“…Sequences were submitted to GeneBank with the following accession numbers: JN975879 and JN975880. Sequences generated in this study were compared with those downloaded from GenBank database obtained from T. aestivum-T. uncinatum and T. mesentericum fruiting bodies of known geographical origin [2,3,5,11,22].…”
Section: Molecular Analysesmentioning
confidence: 99%
“…were considered two different species with different geographical distributions, with T. aestivum only growing in the southernmost parts of Europe [1]. Morphological and molecular investigations in the mid 2000s suggested that the two are the same species and hence the older name, T. aestivum, should be used [2,3]. Consequently, T. aestivum has the widest distribution of any of the edible truffles [1], being found from Spain to eastern Europe and from Gotland, Sweden, to North Africa [4] and has a very broad genetic diversity [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the development of controls for commercial fraud in the truffle market as well as inoculated host seedlings. In recent years, several studies have focused on truffle phylogeny using several loci, and these have allowed the main species to be clearly defined (15,31,36,(51)(52)(53)56). As an example, Wang et al (51,52) investigated the European and Asian truffle phylogeny by sequencing several genomic loci.…”
mentioning
confidence: 99%
“…These authors confirmed that T. melanosporum is phylogenetically related to T. indicum, while T. magnatum is related to T. mesentericum and T. aestivum. The intraspecific ITS variability in T. magnatum, T. melanosporum, T. mesentericum, T. aestivum, and T. indicum has been widely investigated (31,35,36,(51)(52)(53)56), and it has been revealed that the most expensive species (T. magnatum and T. melanosporum) have a low level of ITS variability. On the other hand, T. mesentericum, T. aestivum, and T. indicum showed a higher diversity level.…”
mentioning
confidence: 99%